KOMPONEN-KOMPONEN SUPERVISI PENDIDIKAN ISLAM: Sebuah Kajian Konseptual dalam Implementasi Kepemimpinan Pendidikan Islam - Supandi, Supandi; Aini, Kurratul (Fakultas Agama Islam Universitas Islam Madura, 2025)
Educational supervision is one of the important functions in education management which aims to foster, guide, and improve the professionalism of educators in order to achieve optimal learning quality. This article examines conceptually the components of Islamic education supervision and their relevance in the implementation of leadership in madrasas. The study was conducted through a literature study on education supervision theory, education regulation, and expert views, emphasizing the principles of Islamic education management. The results of the study show that effective supervision consists of several interrelated components, namely: supervision objectives, planning, implementation, supervision techniques (individual and group), instruments, evaluation, and follow-up. Each component has a strategic role in ensuring that the supervision process runs systematically, directed, and sustainable. The implementation of structured supervision will have a positive impact on improving teachers' teaching skills, implementing active, creative, effective, and fun learning (PAKEM), creating a culture of quality in schools, and improving student learning outcomes. In the context of Islamic education, the application of supervision is not only technical, but also based on the values of coaching, service, and moral responsibility. The conclusion of this study emphasizes that the success of supervision is highly dependent on the synergy of all components, so it needs to be designed and implemented comprehensively and sustainably